Co-morbid cardiometabolic diseases among people living with HIV/AIDS in Cameroon - Ebasone, Peter Vanes (Department of Medicine, 2025)
Background and Purpose: To investigate the effects and mediators of HIV infection and related treatment on the prevalence and incidence of cardiometabolic diseases (CMDs) including hypertension, type 2 diabetes mellitus (T2D), and obesity in people living with HIV (PLWH) in Cameroon. Additionally, three systematic reviews were conducted to assess the global prevalence of hypertension, T2D, and obesity among ART-naïve PLWH; and to evaluate the methodological approaches to mediation analysis and handling missing data in studies on CMDs in PLWH. Methods: The study utilized data from 14,279 PLWH enrolled in the Cameroon arm of the International Epidemiology Databases to Evaluate AIDS (IeDEA). Analyses comprised multinomial and binomial logistic regressions, causal mediation analysis, and Cox proportional hazards regression. Systematic reviews were conducted by searching multiple databases, pooling the prevalence rates of hypertension, T2D, and obesity using a random-effects meta-analysis. Results: In Cameroon, significant determinants of hypertension and T2D included age over 50 years, male sex, and overweight/obesity. ART use was linked to lower odds of T2D, and BMI partially mediated the relationship between ART use and hypertension. Prevalence of overweight/obesity was 37.7% overall, and higher in females. Older age, female sex, and higher CD4 count were associated with increased odds of overweight/obesity, while current smoking was linked to reduced odds. The incidence rate of hypertension was 121.1 per 1,000 person-years, with older age, male sex, and overweight/obesity as predictors. ART exposure reduced the risk of hypertension. The systematic review with meta-analysis revealed a global prevalence of 13.6% for hypertension, 4.0% for T2D, and 12.3% for obesity among ART-naïve PLWH. The review on mediation analysis showed increased adoption of casual mediation frameworks but inconsistencies in reporting. The missing data review revealed both under reporting of missing data and how it was handled. Conclusion: The burden of CMDs in PLWH is significant, driven mainly by established risk factors. emphasizing the need for integrated healthcare strategies that address both HIV/AIDS and CMDs. It also underscores the importance of methodological rigor, which significantly impacts the interpretation and reliability of results.